Redução dimensional de partículas de spin s=0,s=1 e s=2 via mecanismo de Kaluza-Klein - Gracia, Gabriel Brandão de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this graduate work we will perform the dimensional reduction of particles of spin s=0, s=1 and s=2 via Kaluza Klein mechanism. The method of Kaluza-Klein dimensional reduction is introduced by the dimensional reduction from D to D 􀀀1 dimensions of the action that describes a massless spin 0 particle, the Maxwell action and the Linearized Einsten Hilbert action. The actions obtained in D 􀀀 1 dimensions by this procedure are analyzed by the classical and the quantum point of view. On the chapter 5 we use this method to obtain a gauge invariant massive eletrodynamics in D = 1 + 1 dimensions from the dimensional reduction of the linearized K-term of the New massive gravityin D = 2 + 1 dimensions. On the chapter 6 the actions TDiiff and WTDiff are presented and we perform its dimensional reductions. On the chapters 7 and 8 we perform the dimensional reduction of the massless limit of the Sa1 and SnFP actions respectively

Neste trabalho de graduação vamos realizar a redução dimensional de partículas de spin s=0, s=1 e s=2 via mecanismo de Kaluza-Klein. O método da redução dimensional Kaluza-Klein é introduzido pela redução dimensional de D para D􀀀1 dimensões da ação que descreve uma partícula de spin 0 sem massa, da ação de Maxwell e da ação de Einstein Hilbert linearizada. As ações obtidas em D􀀀1 dimensões s~ao analisadas pelo ponto de vista clássico e quântico. No capitulo 5 usamos esse método para obter uma eletrodinâmica massiva invariante por simetria de gauge em D = 1+1 dimensões a partir da redução dimensional do termo K linearizado da New massive gravityem D = 2 + 1 dimensões. No capitulo 6 as ações TDiiff e WTDiiff são apresentadas e fazemos as suas reduções dimensionais. Nos capitulos 7 e 8 fazemos a redução dimensional do limite de massa nula das ações Sa1 e SnFP respectivamente
Keywords: Teoria de campos (Física); Kaluza-Klein, Teorias de; Movimento rotacional; Field theory (Physics)